Ukázka rozvíjení matematické pregramotnosti v kontextu využití digitální pomůcky Bee-Bot (Elementary Mathematics Education Journal, 2024)
Title in English: An example of the development of mathematical pre-literacy in the context of using the Bee-Bot digital tool